A Profilaxia Pré Exposição (PrEP) à infecção pelo HIV no estado de Minas Gerais: avaliação de sua implantação, acompanhamento antes e durante a pandemia de covid-19 (de janeiro de 2018 a dezembro de 2021) - Mayara Cristina Marques de Almeida (2023)
The Pre-Exposure Prophylaxis to HIV (PrEP) was incorporated into the Unified Health System (SUS) in 2017, and was successfully implemented in Minas Gerais in 2018. PrEP is an HIV prevention method that consists of daily use or on demand tablet of Tenofovir + Emtricitabine to mitigate the risk of acquiring HIV infection. The main objective of this study is to analyze the implementation of Pre-Exposure Prophylaxis (PrEP) to HIV in the Unified Health System (SUS) before and during the Covid-19 pandemic, through the monitoring of the Medication Logistic Control System (SICLOM), between January 2018 and December 2021. This is a retrospective cohort study, conducted using data from users registered in SICLOM, Stata software was used for data analysis and the results were presented in descriptive form. Among the 2,353 users registered to start PrEP, only 1,025 remained until the end of the study. The average age was 33 years old; 53.97% classified themselves as white; 68.08% reported that they had 12 years or more of education; 75.22% identified themselves as homosexual/ gay/ lesbian and 86.23% defined themselves as male. As for the vulnerability factors for HIV infection, 48.90% reported the use of alcohol and 28.45% the use of illicit drugs and 9.57% reported transactional sex. In the first medical appointment, 10.62% of users reported that they did not use condoms in all sexual relations. In the last medical appointment, this percentage was 23.22% of users. There was no significant increase in the number of sexual partnerships, but an incidence of Syphilis of 6.91/100% population was observed. The study data show that the Covid19 pandemic scenario may have interfered with the number of people using PrEP, given the decrease in registrations in 2020. Despite a considerable number of people who used alcohol and drugs, there was no interference in adherence to treatment and the effectiveness of PrEP to prevent new HIV infections can be observed, considering that there was only one user diagnosed with HIV. The analysis of data from this study may be useful for the improvement and expansion of SUS policies for the prevention of HIV and other STIs.